2011
DOI: 10.1055/s-0031-1295436
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Levels in Neonates with Congenital Diaphragmatic Hernia

Abstract: Cytokines play an important role in immune regulation and fetal lung development. The systemic inflammatory response in newborns with congenital diaphragmatic hernia (CDH) has not been characterized so far. We compared various concentrations of cytokines in serum from newborns with CDH and in healthy term neonates. We analyzed cytokine patterns of CDH newborns under extracorporeal membrane oxygenation (ECMO) and mechanical ventilation (MV).38 newborns with CDH were included: ECMO group (n=13) and non-ECMO grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
1
19
0
2
Order By: Relevance
“…It is worth noting that STAT2 is a pivotal component of the IFN-induced transcriptional machinery and mediates anti-growth and apoptotic effects [39,40]. Moreover, IFN-α was demonstrated to be significantly increased in newborns with CDH [41]. Considering all these observations, one question that remains unexplored is whether CDH progression causes disturbances in the IFN-α -STAT2 signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that STAT2 is a pivotal component of the IFN-induced transcriptional machinery and mediates anti-growth and apoptotic effects [39,40]. Moreover, IFN-α was demonstrated to be significantly increased in newborns with CDH [41]. Considering all these observations, one question that remains unexplored is whether CDH progression causes disturbances in the IFN-α -STAT2 signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined the levels of various cytokines in the blood of neonates with CDH, drawn shortly after birth and longitudinally over 4 days (22). The authors detected elevated levels of several pro-inflammatory cytokines in infants with CDH compared to unaffected controls, although blood from patients with CDH was drawn after the initial resuscitation while control blood was obtained from the umbilical cord.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been shown that CDH is associated with a systemic inflammatory response, with increased levels of chemokines and cytokines in the serum of patients with CDH [15, 16]. We therefore used immunohistochemistry with antibody against F4/80 to target macrophages as a sign of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This hypertrophy and accumulation leads to thickened vessel walls and decreased vessel lumens, further contributing to PH. Studies have also shown that there is an increased systemic inflammatory response in patients with CDH [15, 16], however the relationship between this and pulmonary vascular remodeling is still unclear. Unfortunately, therapies for the PH of CDH have not been developed because the mechanisms driving the pulmonary vascular remodeling that leads to the development of PH in CDH remain unknown.…”
Section: Introductionmentioning
confidence: 99%